THE DEVELOPMENT OF LEARNING MEDIA BASED INTERACTIVE MATH COMIC FOR STUDENTS OF VIII GRADE JUNIOR HIGH SCHOOL - Niniwati Niniwati; Rahmanda Saputra; Puspa Amelia (Prima: Jurnal Pendidikan Matematika, 2023)
The ability of teachers to take advantage of technological developments in learning is highly expected so that students' attention increases in following the Learning process, one obstacle faced by students is the difficulty of understanding the material of cubes and blocks and their formulas. The purpose of this study is to develop interactive comic learning media that is expected to solve problems faced by students and teachers in learning. This Learning Media will be packaged in the form of an interactive Learning CD. This type of research is development research or Development Research. The development research model that the author uses is a computer-aided learning product development model (PBK). Validation is carried out by experts consisting of two lecturers and one teacher to see if this learning media is valid. From the results of the validity test questionnaire analysis conducted by the validator, it can be concluded that the overall validation results for interactive mathematics comic learning media obtained were 87.50 with valid criteria. While the practicality test was carried out by 26 students to see whether this learning media was practical to use or not. From the results of the analysis of student  practicality questionnaire sheets, it was obtained that overall  student assessment of the learning media used was 89.29% with practical criteria.